PENGENDALIAN SOSIAL WAKA KESISWAAN PADA SISWA YANG TIDAK SHALAT ASHAR BERJAMAAH DI SMA ISLAMIYAH - Moeslim, Bahariawan; Budjang A, Gusti; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe thesis discussed â€œPengendalian Sosial oleh Waka Kesiswaan Pada Siswa yang Tidak Melaksanakan Shalat Ashar Berjamaah di SMA Islamiyah Pontianakâ€. The problem of this research was that Social control by headmaster-vice by the student did not practice Ashar prayer in SMA Islamiyah Pontianak with the sub problems how the social control preventif, curative, repressive by headmaster-vice to the student did not practice Ashar prayer in SMA Islamiyah Pontianak. This research used descriptive method in qualitative. The result shoed that (1) preventive social control has been done by headmaster-vice. Before Ashar prayer, the vice-headmaster usually asked to the students and gave instruction to the students to Ashar prayer in the mosque; he gave verbally guidance when in Islam religion subject, and then counseled to his students that never Ashar prayer in the mosque. (2) Curative social control has been done by the vice-headmaster. The evidence that he would gave the warning to the students if they do not Ashar prayer together. (3) Repressive social control has been done by the vice-headmaster. The evidence that he would gave twice punishment to the students if they do not Ashar prayer together in the mosque.Keywords: Ashar Prayer together, Social Control, the students, the Vice-Headmaster